Editorial - Valer Lopera, Lucio Máximo (2014)
Scientific research to produce science and technology for our society It is an immense task priority and as such practice in our university becomes relevant. In this regard, it is important to note that the publication of the Journal of the Institute of Educational Research is an academic practice, whose purpose is to disseminate results of research topics and we hope our dear readers analyze from a critical perspective to explore their limitations and strengths.